Elucidating Tuta absoluta (Meyrick) invasion and enhancing its management in Eastern Africa : spread, socio-ecological impacts, and potential of a newly imported larval parasitoid for classical biological control Eastern in Africa - Aigbedion-Atalor, Pascal Osabhahiemen (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2021)
Agriculture is a fundamental source of sustainable livelihoods in sub-Saharan Africa and millions of people in the region rely solely on small-scale farming for their food security. However, the impacts of invasive alien species (IAS) on crop production are serious, and there is no sign of this abating. Among the recent IAS that have invaded Africa in the last decade, the South American tomato pinworm Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) has been one of the most damaging. Following its first record in the Maghreb region of Africa in 2008, T. absoluta rapidly spread throughout Africa with substantial impacts on tomato production, often causing 100% yield loss. Management options adopted against T. absoluta by tomato growers in Africa have been based on the use of synthetic insecticides. While chemical insecticide applications are an important component of an integrated pest management programme, misuse and over-reliance often exacerbates the impacts of T. absolutadue to the development of resistance to commonly used active substances, increasing the fitness of the pest. This thesis sought to understand the socio-economic impacts of the spread of T. absoluta in Eastern Africa and provide effective sustainable pest management strategies to reduce its impacts below economic thresholds. Mapping surveys of Tabsoluta were conducted in 226 tomato agro-ecosystems across four eastern countries (Kenya, Sudan, Tanzania, and Uganda) Eastern Africa from 2016 to 2018 to determine the spatiotemporal distribution of the pest. The impacts of T. absoluta on the livelihoods of tomato growers were also assessed. Here, 200 tomato growers in Kenya were interviewed using a semi-structured questionnaire. Although T. absoluta, a recent invader, was distributed at high infestation levels throughout the subregion (all four countries) and was considered as the most damaging invasive alien species of agriculturally sustainable livelihoods. The arrival of T. absoluta in the subregion has resulted in livelihood losses and increased the cost of tomato production and price of the fruit, and the frequency of pesticide applications. The impact of this pest and the and the absence of effective indigenous natural enemies of the pest in Eastern Africa, was the rationale for the importation of a larval parasitoid, Dolichogenidea gelechiidivoris Marsh Syn.: Apanteles gelechiidivoris Marsh) (Hymenoptera: Braconidae), of T. absoluta from Peru into the quarantine facility of the International Centre of Insect Physiology and ecologyz(icipe), in Kenya. Pre-release assessments on the parasitzation potential of D. gelechiidivoris, encompassing host larval preference and the host suitability, and its reproductive strategy, for classical biological control of T. absoluta in Africa were conducted. Dolichogenidea gelechiidivoris females preferentially oviposited in early (1st and 2nd) larval instars of T. absoluta but parasitized and completed development in all four instars of the host. Host instar did not affect D. gelechiidivoris sex-ratio but females reared on the first instar had significantly fewer eggs than when reared in late larval instars (3rd and 4th). Females of the parasitoid emerged with a high mature egg load which peaked 2 d post-eclosion. The females of D. gelechiidivoris survived 8.51Â±0.65 d and produced 103Â±8 offspring per female at 26Â±4Â°C (range: 24 to 29Â°C) and 50"“70% relative humidity (RH) in the presence of males and fed honey-water (80% honey). Increasing maternal age decreased the proportion of female offspring. Under the aforementioned laboratory conditions, the Gross and Net reproductive rates were 72 and 39.5 respectively, while the mean generation time was 20 d. The estimated intrinsic rate of natural increase was 0.18. These findings indicate that D. gelechiidivorisis a potential biological control agent of T. absoluta and should be considered for augmentative/inundative release in Kenya and across Africa following host specificity testing and risk assessments. The nature of the interaction between D. gelechidivoris and the predatory mirid bug Nesidiocoris tenuis(Reuter) (Hemiptera: Miridae), an important and widespread natural enemy of T. absoluta in Africa was evaluated because N. tenuis, although being a voracious predator of T. absoluta eggs, it can also prey on the early host larval instars (1st and 2nd) which are the preferred oviposition host stages of D. gelechiidivoris. Here, the impact of N. tenuis feeding on T. absoluta and the effects on D. gelechiidivoris performance was tested. Regardless of the order of introductions (i.e. the sequence of combination with D. gelechiidivoris) and densities (i.e. number of N. tenuis combined with D. gelechiidivoris), there was no intraguild predation by N. tenuis on D. gelechiidivorisas there was little host larval feeding behaviour. Also, the presence of N. tenuis did not affect the oviposition performance of D. gelechiidivoris. Further investigations revealed that the combined efficacy of N. tenuis and D. gelechiidivorison T. absoluta population was significantly higher than either natural enemy alone, thus contributes to the data supporting the release of D. gelechiidivoris in Africa. In concluding, integrating D. gelechiidivoris and N. tenuis in the management of T. absolut could potentially reduce yield losses in tomato in Eastern Africa where the socio-economic impacts of the pest are very serious.
Keywords: Tuta absoluta -- Biological control; Tomatoes -- Diseases and pests -- Africa, East; Braconidae; Gelechiidae -- Biological control -- Africa, East; Insects as biological pest control agents -- Africa, East